Ending preventable maternal and newborn deaths due to infection. (October 2016) - Desale, Meghana; Thinkhamrop, Jadsada; Lumbiganon, Pisake; Qazi, Shamim; Anderson, Jean
Abstract : Over 300, 000 maternal deaths occur each year, 11% of which are thought to be due to infectious causes, and approximately one million newborns die within the first week of life annually due to infectious causes. Infections in pregnancy may result in a variety of adverse obstetrical outcomes, including preterm delivery, pre-labor rupture of membranes, stillbirth, spontaneous abortion, congenital infection, and anomalies. This paper reviews the burden of disease due to key infections and their contribution to maternal, perinatal, and newborn morbidity and mortality, as well as key interventions to prevent maternal and newborn deaths related to these infections. Research needs include more accurate clinical and microbiologic surveillance systems, validated risk stratification strategies, better point-of-care testing, and identification of promising vaccine strategies. Highlights: Lifelong antiretroviral therapy is recommended for pregnant women with human immunodeficiency virus (HIV) in low-resource settings. HIV+ pregnant women should be screened at each visit for tuberculosis-related symptoms. Intermittent preventive treatment and use of insecticide-treated bed nets are important malaria-preventive measures in pregnancy. Intrapartum antibiotic prophylaxis for Group B Streptococcus colonization and with other risk factors decreases risk of early neonatal sepsis. Accurate, rapid, point-of-care diagnostic tests for syphilis are now available.